Drying Halves Decomposition Rates in River Networks by Decreasing Decomposer Diversity - Rubén del Campo; Thibault Datry; Arnaud Foulquier; Naiara López‐Rojo; Loïc Chalmandrier; Zoltán Csabai; David Cunillera‐Montcusí; Amaia A. Rodeles; Francisco J. Peñas; Bálint Pernecker; Núria Bonada; José Barquín; et al. (Global Change Biology, 2026)
River drying is intensifying worldwide due to climate change and increasing water abstraction, with major consequences for riverine biodiversity and ecosystem functioning. In river networks, drying not only alters local environmental conditions but also disrupts hydrological connectivity, reshaping the movement of organisms and resources at the river network scale. Leaf litter decomposition—a key ecosystem function in freshwater systems—is particularly sensitive to changes in the structure of decomposer communities. We hypothesized that spatiotemporal patterns of drying regulate decomposition by altering the diversity and composition of detritivorous macroinvertebrates, bacteria and fungi. We combined data from six European river networks spanning a wide latitudinal gradient to assess how local drying intensity and regional hydrological connectivity affect decomposition through changes in these decomposer groups. We found that short drying events (≤ 6 dry days) reduced decomposition rates by up to 50% mainly mediated by changes in the composition and diversity of decomposer communities. Drying decreased the diversity of groups contributing to decomposition, shifting the control of this function from a balanced contribution of fungi, bacteria and detritivores in perennial rivers to dominance by dry‐tolerant but less efficient bacteria in drying rivers. These community shifts persisted for months after flow resumption, causing sustained reductions in decomposition also in flowing conditions. Regional hydrological connectivity alleviated these negative effects of local drying by facilitating the recovery of more efficient aquatic decomposers. However, this effect depended on the river network. In more arid networks, stronger fragmentation hindered the recovery of decomposer communities after flow resumption. Overall, our results evidence that spatiotemporal patterns of drying can regulate the linkages between community structure and ecosystem functioning in river networks. As drying events become more frequent and prolonged, shifts in decomposers' diversity are likely to alter carbon cycling and energy fluxes in freshwater ecosystems under global change.

Forest type consistently shapes bird communities across seasons: Insights from passive acoustic monitoring - Esther Sophie Felgentreff; David Singer; Markus Bernhardt-Römermann (Forest Ecology and Management, 2026)

A chromosome-scale reference genome and integrative transcriptome provide insight into tissue- and stress-specific responses in tetraploid sainfoin (Onobrychis viciifolia) - Cuong V. Nguyen; Dustin Cram; Halim Song; Rodrigo Ortega Polo; Hari Poudel; Bill Biligetu; Kimberley Burton Hughes; Surya Acharya; David Konkin; Stacy D. Singer (Planta, 2026)
Main conclusion A haplotype-resolved, chromosome-scale AAC Mountainview sainfoin genome sequence along with organelle assemblies, methylome, and comparative tissue/stress-specific transcriptomes provide a solid foundation to support downstream sainfoin breeding efforts. Abstract Sainfoin ( Onobrychis viciifolia Scop.) is an outcrossing, perennial forage crop valued for its leguminous nature, nutritional quality, palatability, and production of condensed tannins, which reduce the incidence of pasture bloat in ruminants and improve feed efficiency. However, despite its potential, there remains a paucity of research and breeding efforts focusing on this species. In this study, we report the generation of a haplotype-resolved, chromosome-scale reference genome sequence for a genotype of the tetraploid sainfoin cultivar AAC Mountainview, which was assembled using PacBio HiFi, Oxford Nanopore, Illumina short read, and Hi-C data. The 2.36 Gb assembly resolves all 28 pseudochromosomes, corresponding to 4 haplotypes of the 7 base chromosomes, with high contiguity and gene completeness, as well as reference-grade long terminal repeat (LTR) assembly index (LAI) scores across all haplotypes. Nanopore-based methylation profiling revealed typical gene body CG methylation, as well as high levels of transposable element methylation. We annotated 117,890 high-confidence protein-coding genes and identified large tandem arrays of rDNA localized on unanchored but chromosome-associated scaffolds. Mitochondrial and chloroplast genomes were also successfully assembled for this genotype. Furthermore, tissue- and stress-specific transcriptomic profiling revealed both shared and distinct gene expression responses across tissue and stress types. Allele-specific expression analysis showed largely balanced haplotype activity, with subtle but consistent shifts in allelic dominance under stress. The data provided in this study offer a valuable resource for downstream breeding endeavors in this promising forage crop.

Seasonal variability in the hydrogeochemical behavior and metal fluxes of acid mine drainage: Implications for long-term output and treatment - David M. Singer; Rachel Izworski; Annika Dudik; Allyson C. Tessin (Journal of Contaminant Hydrology, 2026)

Diel and seasonal vocal activity patterns revealed by passive acoustic monitoring suggest expert recommendations for breeding bird surveys need adjustment - David Singer; Johannes Kamp; Hermann Hondong; Andreas Schuldt; Jonas Hagge (Journal of Ornithology, 2026)
Species identification and recording in breeding bird surveys vastly rely on the registration of avian calls and songs. Despite comprehensive expert knowledge on species-specific activity patterns, data-based analyses of vocal activity patterns are lacking. Recent advances in passive acoustic monitoring allow the direct measurement of bird vocal activity at very high temporal resolution. We conducted a comprehensive survey, recording 25,000 h of audio data at 256 forest sites in Lower Saxony, Germany, to investigate vocal activity patterns of the European forest bird community. Our results reveal a high degree of inter-specific variability in seasonal and diel vocal activity patterns, including strong circular patterns along the day–night cycle and a significant seasonal component. Comparing acoustic detectability to species-specific survey recommendations revealed critical temporal discrepancies for 64.2% of species, and standard protocols (sunrise to 4 h after sunrise) showed discrepancies for 41.5% of species. This highlights the potential for temporal survey optimization to reduce imperfect detection and increase accuracy and precision. Emphasis should be given to the hours before and after sunrise and also sunset for sampling less detectable species. Combining observer-based surveys with passive acoustic monitoring might leverage the strengths of both methods. Our results also emphasize the potential of continuous recording schedules in passive acoustic monitoring to capture diverse temporal patterns. This study provides a baseline for future research on vocal activity patterns across habitats, throughout the year, and regarding anthropogenic impacts. Our findings may raise awareness among ornithologists about the sources of variation in acoustic detectability and its implications for breeding bird surveys, highlighting potential for methodological adjustments in survey timing and consequences for carful interpretation of bird surveys.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Comparing probabilistic and entropic strategies for tracking the fragility of design space reduction decisions in set-based design - Joseph Van Houten; Austin A. Kana; David Singer; Matthew Collette (Ocean Engineering, 2025)

Avenues towards reconciling wild and managed bee proponents - Alexis L. Beaurepaire; Katja Hogendoorn; David Kleijn; Gard W. Otis; Simon G. Potts; Theresa L. Singer; Samuel Boff; Christian Pirk; Josef Settele; Robert J. Paxton; Nigel E. Raine; Simone Tosi; et al. (Trends in Ecology & Evolution, 2025)

Functional plasticity of HCO3– uptake and CO2 fixation in Cupriavidus necator H16 - Justin Panich; Emili Toppari; Sara Tejedor-Sanz; Bonnie Fong; Eli Dugan; Yan Chen; Christopher J. Petzold; Zhiying Zhao; Yasuo Yoshikuni; David F. Savage; Steven W. Singer (Bioresource Technology, 2024)

Does the Southern Green Anaconda, Eunectes murinus, seek areas of high prey concentration in southeastern Peru? - Patrick S. Champagne; Thomas B. Herman; Paul Rosolie; Dylan Singer; Dan Horton; Carter J. Payne; Lucy Dablin; David Colville; Julio Cardenas; Miryam Quevedo; Trevor Avery; Renata Leite Pitman (Food Webs, 2024)

Neighborhood-scale lead (Pb) speciation in Akron, Ohio (USA) soils: primary sources, post-deposition diagenesis, and high concentrations of labile Pb - Nicholas Santoro; David M. Singer; Bridget K. Mulvey; Katrina Halasa; Nadya Teutsch; Allie Shedleski; Madison Wood (Environmental Geochemistry and Health, 2024)
Lead (Pb) poses a significant risk to infants and children through exposure to contaminated soil and dust. However, there is a lack of information on Pb speciation and distribution at the neighborhood-scale. This work aimed to determine: (1) the distribution of acid-extractable (labile) Pb and other metals ([M] AE ) in two neighborhoods in Akron, Ohio (USA) (Summit Lake and West Akron; n = 82 samples); and (2) Pb speciation and potential sources. Total metal concentration ([M] T ) and [M] AE was strongly correlated for Pb and Zn (R 2 of 0.66 and 0.55, respectively), corresponding to 35% and 33% acid-extractability. Lead and Zn exhibited a strong positive correlation with each other (R 2 = 0.56 for M T and 0.68 for M AE ). Three types of Pb-bearing phases were observed by electron microscopy: (1) galena (PbS)-like (5–10 μm); (2) paint chip residuals (10–20 μm); and (3) Pb-bearing Fe-oxides (20 μm). Isotope ratio values for Pb AE were 1.159 to 1.245 for 206 Pb/ 207 Pb, and 1.999 to 2.098 for 208 Pb/ 206 Pb, and there was a statistically significant difference between the two neighborhoods ( p = 0.010 for 206 Pb/ 207 Pb and p = 0.009 for 208 Pb/ 206 Pb). Paint and petrol are the dominant sources of Pb, with some from coal and fly ash. Lead speciation and distribution is variable and reflects a complex relationship between the input of primary sources and post-deposition transformations. This work highlights the importance of community science collaborations to expand the reach of soil sampling and establish areas most at risk based on neighborhood-dependent Pb speciation and distribution for targeted remediation.

Unravelling the distribution of three Ammonia species (Foraminifera, Rhizaria) in French Atlantic Coast estuaries using morphological and metabarcoding approaches - Marie P.A. Fouet; Magali Schweizer; David Singer; Julien Richirt; Sophie Quinchard; Frans J. Jorissen (Marine Micropaleontology, 2024)

It's time to consider the Arcellinida shell as a weapon - Kenneth Dumack; Enrique Lara; Clément Duckert; Elizaveta Ermolaeva; Ferry Siemensma; David Singer; Valentyna Krashevska; Mariusz Lamentowicz; Edward A.D. Mitchell (European Journal of Protistology, 2024)

Unlocking foraminiferal genetic diversity on estuarine mudflats with eDNA metabarcoding - David Singer; Marie P.A. Fouet; Magali Schweizer; Aurélia Mouret; Sophie Quinchard; Frans J. Jorissen (Science of The Total Environment, 2023)

A framework for evaluating inherent biases within ship design tools - Michael J. Sypniewski; David J. Singer (Ocean Engineering, 2023)

Lime slurry treatment of soils developing on abandoned coal mine spoil: Linking contaminant transport from the micrometer to pedon-scale - Daniel L. Wood; Kortney A. Cole; Elizabeth M. Herndon; David M. Singer (Applied Geochemistry, 2023)

Discrepancies between prokaryotes and eukaryotes need to be considered in soil DNA ‐based studies - Enrique Lara; David Singer; Stefan Geisen (Environmental Microbiology, 2022)
Summary Metabarcoding approaches are exponentially increasing our understanding of soil biodiversity, with a major focus on the bacterial part of the microbiome. Part of the soil diversity are also eukaryotes that include fungi, algae, protists and Metazoa. Nowadays, soil eukaryotes are targeted with the same approaches developed for bacteria and archaea (prokaryotes). However, fundamental differences exist between domains. After providing a short historical overview of the developments of metabarcoding applied to environmental microbiology, we compile the most important differences between domains that prevent direct method transfers between prokaryotic and eukaryotic soil metabarcoding approaches, currently dominated by short‐read sequencing. These include the existence of divergent diversity concepts and the variations in eukaryotic morphology that affect sampling and DNA extraction. Furthermore, eukaryotes experienced much more variable evolutionary rates than prokaryotes, which prevent capturing the entire eukaryotic diversity in a soil with a single amplification protocol fit for short‐read sequencing. In the final part we focus on future potentials for optimization of eukaryotic metabarcoding that include superior possibility of functionally characterizing eukaryotes and to extend the current information obtained, such as by adding a real quantitative component. This review should optimize future metabarcoding approaches targeting soil eukaryotes and kickstart this promising research direction.

HIV, pathology and epigenetic age acceleration in different human tissues - Steve Horvath; David T. S. Lin; Michael S. Kobor; Joseph A. Zoller; Jonathan W. Said; Susan Morgello; Elyse Singer; William H. Yong; Beth D. Jamieson; Andrew J. Levine (GeroScience, 2022)
Epigenetic clocks based on patterns of DNA methylation have great importance in understanding aging and disease; however, there are basic questions to be resolved in their application. It remains unknown whether epigenetic age acceleration (EAA) within an individual shows strong correlation between different primary tissue sites, the extent to which tissue pathology and clinical illness correlate with EAA in the target organ, and if EAA variability across tissues differs according to sex. Considering the outsized role of age-related illness in Human Immunodeficiency Virus-1 (HIV), these questions were pursued in a sample enriched for tissue from HIV-infected individuals. We used a custom methylation array to generate DNA methylation data from 661 samples representing 11 human tissues (adipose, blood, bone marrow, heart, kidney, liver, lung, lymph node, muscle, spleen and pituitary gland) from 133 clinically characterized, deceased individuals, including 75 infected with HIV. We developed a multimorbidity index based on the clinical disease history. Epigenetic age was moderately correlated across tissues. Blood had the greatest number and degree of correlation, most notably with spleen and bone marrow. However, blood did not correlate with epigenetic age of liver. EAA in liver was weakly correlated with EAA in kidney, adipose, lung and bone marrow. Clinically, hypertension was associated with EAA in several tissues, consistent with the multiorgan impacts of this illness. HIV infection was associated with positive age acceleration in kidney and spleen. Male sex was associated with increased epigenetic acceleration in several tissues. Preliminary evidence indicates that amyotrophic lateral sclerosis is associated with positive EAA in muscle tissue. Finally, greater multimorbidity was associated with greater EAA across all tissues. Blood alone will often fail to detect EAA in other tissues. While hypertension is associated with increased EAA in several tissues, many pathologies are associated with organ-specific age acceleration.

Soil protist function varies with elevation in the Swiss Alps - Florent Mazel; Lucie Malard; Hélène Niculita‐Hirzel; Erika Yashiro; Heidi K. Mod; Edward A. D. Mitchell; David Singer; Aline Buri; Eric Pinto; Nicolas Guex; Enrique Lara; Antoine Guisan (Environmental Microbiology, 2022)
Summary Protists are abundant and play key trophic functions in soil. Documenting how their trophic contributions vary across large environmental gradients is essential to understand and predict how biogeochemical cycles will be impacted by global changes. Here, using amplicon sequencing of environmental DNA in open habitat soil from 161 locations spanning 2600 m of elevation in the Swiss Alps (from 400 to 3000 m), we found that, over the whole study area, soils are dominated by consumers, followed by parasites and phototrophs. In contrast, the proportion of these groups in local communities shows large variations in relation to elevation. While there is, on average, three times more consumers than parasites at low elevation (400–1000 m), this ratio increases to 12 at high elevation (2000–3000 m). This suggests that the decrease in protist host biomass and diversity toward mountains tops impact protist functional composition. Furthermore, the taxonomic composition of protists that infect animals was related to elevation while that of protists that infect plants or of protist consumers was related to soil pH. This study provides a first step to document and understand how soil protist functions vary along the elevational gradient.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Phylogenetic diversity and dominant ecological traits of freshwater Antarctic Chrysophyceae - Irina Izaguirre; Fernando Unrein; M. Romina Schiaffino; Enrique Lara; David Singer; Vanessa Balagué; Josep M. Gasol; Ramon Massana (Polar Biology, 2021)

Greater topoclimatic control of above‐ versus below‐ground communities - Heidi K. Mod; Daniel Scherrer; Valeria Di Cola; Olivier Broennimann; Quentin Blandenier; Frank T. Breiner; Aline Buri; Jérôme Goudet; Nicolas Guex; Enrique Lara; Edward A. D. Mitchell; Hélène Niculita‐Hirzel; et al. (Global Change Biology, 2020)
Assessing the degree to which climate explains the spatial distributions of different taxonomic and functional groups is essential for anticipating the effects of climate change on ecosystems. Most effort so far has focused on above‐ground organisms, which offer only a partial view on the response of biodiversity to environmental gradients. Here including both above‐ and below‐ground organisms, we quantified the degree of topoclimatic control on the occurrence patterns of >1,500 taxa and phylotypes along a c. 3,000 m elevation gradient, by fitting species distribution models. Higher model performances for animals and plants than for soil microbes (fungi, bacteria and protists) suggest that the direct influence of topoclimate is stronger on above‐ground species than on below‐ground microorganisms. Accordingly, direct climate change effects are predicted to be stronger for above‐ground than for below‐ground taxa, whereas factors expressing local soil microclimate and geochemistry are likely more important to explain and forecast the occurrence patterns of soil microbiota. Detailed mapping and future scenarios of soil microclimate and microhabitats, together with comparative studies of interacting and ecologically dependent above‐ and below‐ground biota, are thus needed to understand and realistically forecast the future distribution of ecosystems.

Correction to: A candidate gene study of intermediate histopathological phenotypes in HIV-associated neurocognitive disorders - Andrew J. Levine; Virawudh Soontornniyomkij; Eliezer Masliah; Janet S. Sinsheimer; Sarah S. Ji; Steve Horvath; Elyse J. Singer; Asha Kallianpur; David J. Moore (Journal of NeuroVirology, 2020)

A candidate gene study of intermediate histopathological phenotypes in HIV-associated neurocognitive disorders - Andrew J. Levine; Virawudh Soontornniyomkij; Eliezer Masliah; Janet S. Sinsheimer; Sarah S. Ji; Steve Horvath; Elyse J. Singer; Asha Kallianpur; David J. Moore (Journal of NeuroVirology, 2020)

Soil protist diversity in the Swiss western Alps is better predicted by topo‐climatic than by edaphic variables - Christophe V. W. Seppey; Olivier Broennimann; Aline Buri; Erika Yashiro; Eric Pinto‐Figueroa; David Singer; Quentin Blandenier; Edward A. D. Mitchell; Hélène Niculita‐Hirzel; Antoine Guisan; Enrique Lara (Journal of Biogeography, 2020)
Aim Trends in spatial patterns of diversity in macroscopic organisms can be well predicted from correlative models, using topo‐climatic variables for plants and animals allowing inference over large scales. By contrast, diversity in soil microorganisms is generally considered as mostly driven by edaphic variables and, therefore, difficult to extrapolate on a large spatial scale based on predictive models. Here, we compared the power of topo‐climatic versus edaphic variables for predicting the diversity of various soil protist groups at the regional scale. Location Swiss western Alps. Taxa Full protist community and nine clades belonging respectively to three functional groups: parasites (Apicomplexa, Peronosporomycetes and Phytomyxea), phagotrophs (Sarcomonadea, Tubulinea and Spirotrichea) and phototrophs (Chlorophyta, Trebouxiophyceae and Diatomeae). Methods We extracted soil DNA from 178 sites along a wide range of elevations with a random‐stratified sampling design. We defined protist Operational Taxonomic Units assemblages by metabarcoding of the V4 region of the rRNA small subunit gene. We assessed and modelled the diversity (Shannon index) patterns of all above‐mentioned taxonomic groups based on topo‐climatic (topography, slope southness, slope steepness and average summer temperature) and edaphic (soil temperature, relative humidity, pH, electroconductivity, phosphorus percentage, carbon/nitrogen, loss on ignition and shale percentage) variables in Generalized Additive Models (GAM). Results The respective significance of topo‐climatic and edaphic variables varied among taxonomic and—to a certain extent—functional groups: while many variables explained significantly the diversity of the three phototrophs this was less the case for the three parasites. Topo‐climatic variables had a better predictive power than edaphic variables, yet predictive power varied among taxonomic groups. Main conclusions Topo‐climatic variables (particularly slope steepness and summer temperature if we consider their significance in the GAMs) were, on average, better predictors of protist diversity at the landscape scale than edaphic variables. However, the predictive power of these variables on diversity differed considerably among taxonomic groups; such relationships may be due to direct and/or indirect (e.g. biotic) influences (like with parasitic taxa, where low predictive power is most likely explained by the absence of information on the hosts’ distribution). Future prospects include using such spatial models to predict hotspots of diversity and disease outbreaks.

Global distribution of Trebouxiophyceae diversity explored by high‐throughput sequencing and phylogenetic approaches - Sebastian Metz; David Singer; Isabelle Domaizon; Fernando Unrein; Enrique Lara (Environmental Microbiology, 2019)
Summary Trebouxiophyceae are a ubiquitous class of Chlorophyta encountered in aquatic and terrestrial environments. Most taxa are photosynthetic, and many acts as photobionts in symbiotic relationships, while others are free‐living. Trebouxiophyceae have also been widely investigated for their use for biotechnological applications. In this work, we aimed at obtaining a comprehensive image of their diversity by compiling the information of 435 freshwater, soil and marine environmental DNA samples surveyed with Illumina sequencing technology in order to search for the most relevant environments for bioprospecting. Freshwater and soil were most diverse and shared more than half of all operational taxonomic units (OTUs), however, their communities were significantly distinct. Oceans hosted the highest genetic novelty, and did not share any OTUs with the other environments; also, marine samples host more diversity in warm waters. Symbiotic genera usually found in lichens such as Trebouxia , Myrmecia and Symbiochloris were also abundantly detected in the ocean, suggesting either free‐living lifestyles or unknown symbiotic relationships with marine planktonic organisms. Altogether, our study opens the way to new prospection for trebouxiophycean strains, especially in understudied environments like the ocean.

Dispersal limitations and historical factors determine the biogeography of specialized terrestrial protists - David Singer; Edward A. D. Mitchell; Richard J. Payne; Quentin Blandenier; Clément Duckert; Leonardo D. Fernández; Bertrand Fournier; Cristián E. Hernández; Gustaf Granath; Håkan Rydin; Luca Bragazza; Natalia G. Koronatova; et al. (Molecular Ecology, 2019)
Recent studies show that soil eukaryotic diversity is immense and dominated by micro‐organisms. However, it is unclear to what extent the processes that shape the distribution of diversity in plants and animals also apply to micro‐organisms. Major diversification events in multicellular organisms have often been attributed to long‐term climatic and geological processes, but the impact of such processes on protist diversity has received much less attention as their distribution has often been believed to be largely cosmopolitan. Here, we quantified phylogeographical patterns in Hyalosphenia papilio , a large testate amoeba restricted to Holarctic Sphagnum ‐dominated peatlands, to test if the current distribution of its genetic diversity can be explained by historical factors or by the current distribution of suitable habitats. Phylogenetic diversity was higher in Western North America, corresponding to the inferred geographical origin of the H. papilio complex, and was lower in Eurasia despite extensive suitable habitats. These results suggest that patterns of phylogenetic diversity and distribution can be explained by the history of Holarctic Sphagnum peatland range expansions and contractions in response to Quaternary glaciations that promoted cladogenetic range evolution, rather than the contemporary distribution of suitable habitats. Species distributions were positively correlated with climatic niche breadth, suggesting that climatic tolerance is key to dispersal ability in H. papilio . This implies that, at least for large and specialized terrestrial micro‐organisms, propagule dispersal is slow enough that historical processes may contribute to their diversification and phylogeographical patterns and may partly explain their very high overall diversity.

Anthropogenic fragmentation of landscapes: mechanisms for eroding the specificity of plant–herbivore interactions - Robert Bagchi; Leone M. Brown; Chris S. Elphick; David L. Wagner; Michael S. Singer (Oecologia, 2018)

Environmental filtering and phylogenetic clustering correlate with the distribution patterns of cryptic protist species - David Singer; Anush Kosakyan; Christophe V. W. Seppey; Amandine Pillonel; Leonardo D. Fernández; Diego Fontaneto; Edward A. D. Mitchell; Enrique Lara (Ecology, 2018)
The community composition of any group of organisms should theoretically be determined by a combination of assembly processes including resource partitioning, competition, environmental filtering, and phylogenetic legacy. Environmental DNA studies have revealed a huge diversity of protists in all environments, raising questions about the ecological significance of such diversity and the degree to which they obey to the same rules as macroscopic organisms. The fast‐growing cultivable protist species on which hypotheses are usually experimentally tested represent only a minority of the protist diversity. Addressing these questions for the lesser known majority can only be inferred through observational studies. We conducted an environmental DNA survey of the genus Nebela , a group of closely related testate (shelled) amoeba species, in different habitats within Sphagnum ‐dominated peatlands. Identification based on the mitochondrial cytochrome c oxidase 1 gene, allowed species‐level resolution as well as phylogenetic reconstruction. Community composition varied strongly across habitats and associated environmental gradients. Species showed little overlap in their realized niche, suggesting resource partitioning, and a strong influence of environmental filtering driving community composition. Furthermore, phylogenetic clustering was observed in the most nitrogen‐poor samples, supporting phylogenetic inheritance of adaptations in the group of N. guttata . This study showed that the studied free‐living unicellular eukaryotes follow to community assembly rules similar to those known to determine plant and animal communities; the same may be true for much of the huge functional and taxonomic diversity of protists.

Brain-specific HIV Nef identified in multiple patients with neurological disease - Susanna L. Lamers; Gary B. Fogel; Enoch S. Liu; Andrew E. Barbier; Christopher W. Rodriguez; Elyse J. Singer; David J. Nolan; Rebecca Rose; Michael S. McGrath (Journal of NeuroVirology, 2018)

Structural bias in aggregated species‐level variables driven by repeated species co‐occurrences: a pervasive problem in community and assemblage data - Bradford A. Hawkins; Boris Leroy; Miguel Á. Rodríguez; Alexander Singer; Bruno Vilela; Fabricio Villalobos; Xiangping Wang; David Zelený (Journal of Biogeography, 2017)
Aim Species attributes are often used to explain diversity patterns across assemblages/communities. However, repeated species co‐occurrences can generate spatial pattern and strong statistical relationships between aggregated attributes and richness in the absence of biological information. Our aim is to increase awareness of this problem. Location North America. Methods We generated empirical species richness patterns using two data structures: (1) birds gridded from range maps and (2) tree communities from the US Forest Service's Forest Inventory and Analysis. We analysed richness using linear regression, regression trees, generalized additive models, geographically weighted regression and simultaneous autoregression, with ‘random intrinsic variables’ as predictors generated by assigning random numbers to species and calculating averages in assemblages. We then generated simulations in which species with cohesive or patchy distributions are placed with respect to the North American temperature gradient with or without a broad‐scale richness gradient. Random intrinsic variables are again used as predictors of richness. Finally, we analysed one simulated scenario with random intrinsic variables as both response and predictor variables. Results The models of bird and tree richness often explained moderate to large proportions of the variance. Regression trees, geographically weighted regression and simultaneous autoregression were very sensitive to the problem; generalized additive models were moderately affected, as was multiple regression to a lesser extent. In the virtual data, the variance explained increased with increasing species co‐occurrences, but neither range cohesion, a richness gradient nor spatial autocorrelation in predictors had major impacts on the variance explained. The problem persisted when the response variable was also a random intrinsic variable. Main conclusions Repeated species co‐occurrences can generate strong spurious relationships between richness and aggregated species attributes. It is important to realize that models utilizing assemblage variables aggregated from species‐level values, as well as maps illustrating their spatial patterns, cannot be taken at face value.

Microbial eukaryote communities exhibit robust biogeographical patterns along a gradient of Patagonian and Antarctic lakes - M. Romina Schiaffino; Enrique Lara; Leonardo D. Fernández; Vanessa Balagué; David Singer; Christophe C. W. Seppey; Ramon Massana; Irina Izaguirre (Environmental Microbiology, 2016)
Summary Microbial eukaryotes play important roles in aquatic ecosystem functioning. Unravelling their distribution patterns and biogeography provides important baseline information to infer the underlying mechanisms that regulate the biodiversity and complexity of ecosystems. We studied the distribution patterns and factors driving diversity gradients in microeukaryote communities (total, abundant, uncommon and rare community composition) along a latitudinal gradient of lakes distributed from Argentinean Patagonia to Maritime Antarctica using both denaturing gradient gel electrophoresis (DGGE) and high‐throughput sequencing (Illumina HiSeq). DGGE and abundant Illumina operational taxonomic units (OTUs) showed both decreasing richness with latitude and significant differences between Patagonian and Antarctic lakes communities. In contrast, total richness did not change significantly across the latitudinal gradient, although evenness and diversity indices were significantly higher in Patagonian lakes. Beta‐diversity was characterized by a high species turnover, influenced by both environmental and geographical descriptors, although this pattern faded in the rare community. Our results suggest the co‐existence of a ‘core biosphere’ containing reduced number of abundant/dominant OTUs on which classical ecological rules apply, together with a much larger seedbank of rare OTUs driven by stochastic and reduced dispersal processes. These findings shed new light on the biogeographical patterns and forces structuring inland microeukaryote composition across broad spatial scales.

Influence of Weather, Wetland Availability, and Mallard Abundance on Productivity of Great Lakes Mallards (Anas platyrhynchos) - Howard V. Singer; David R. Luukkonen; Llwellyn M. Armstrong; Scott R. Winterstein (Wetlands, 2016)

Multilevel analysis of neuropathogenesis of neurocognitive impairment in HIV - Andrew J. Levine; Virawudh Soontornniyomkij; Cristian L. Achim; Eliezer Masliah; Benjamin B. Gelman; Janet S. Sinsheimer; Elyse J. Singer; David J. Moore (Journal of NeuroVirology, 2016)

Accelerated epigenetic aging in brain is associated with pre-mortem HIV-associated neurocognitive disorders - Andrew J. Levine; Austin Quach; David J. Moore; Cristian L. Achim; Virawudh Soontornniyomkij; Eliezer Masliah; Elyse J. Singer; Benjamin Gelman; Natasha Nemanim; Steve Horvath (Journal of NeuroVirology, 2016)

Comment on “Metallic Mineral Resources in the Twenty-First Century: I. Historical Extraction Trends and Expected Demand” by Alberto E. Patino Douce, in Natural Resources Research DOI: 10.1007/s11053-015-9266-z - Donald A. Singer; W. David Menzie (Natural Resources Research, 2016)

Beyond climate change attribution in conservation and ecological research - Camille Parmesan; Michael T. Burrows; Carlos M. Duarte; Elvira S. Poloczanska; Anthony J. Richardson; David S. Schoeman; Michael C. Singer (Ecology Letters, 2013)
There is increasing pressure from policymakers for ecologists to generate more detailed ‘attribution’ analyses aimed at quantitatively estimating relative contributions of different driving forces, including anthropogenic climate change ( ACC ), to observed biological changes. Here, we argue that this approach is not productive for ecological studies. Global meta‐analyses of diverse species, regions and ecosystems have already given us ‘ very high confidence’ [ sensu Intergovernmental Panel on Climate Change ( IPCC )] that ACC has impacted wild species in a general sense. Further, for well‐studied species or systems, synthesis of experiments and models with long‐term observations has given us similarly high confidence that they have been impacted by regional climate change (regardless of its cause). However, the role of greenhouse gases in driving these impacts has not been estimated quantitatively. Should this be an ecological research priority? We argue that development of quantitative ecological models for this purpose faces several impediments, particularly the existence of strong, non‐additive interactions among different external factors. However, even with current understanding of impacts of global warming, there are myriad climate change adaptation options already developed in the literature that could be, and in fact are being, implemented now.

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Erratum to: Regional areas and widths of the midsagittal corpus callosum among HIV-infected patients on stable antiretroviral therapies - David F. Tate; Mehul Sampat; Jaroslaw Harezlak; Mark Fiecas; Joseph Hogan; Jeffrey Dewey; Daniel McCaffrey; Daniel Branson; Troy Russell; Jared Conley; Michael Taylor; Giovanni Schifitto; et al. (Journal of NeuroVirology, 2011)

Regional areas and widths of the midsagittal corpus callosum among HIV-infected patients on stable antiretroviral therapies - David F. Tate; Mehul Sampat; Jaroslaw Harezlak; Mark Fiecas; Joseph Hogan; Jeffrey Dewey; Daniel McCaffrey; Daniel Branson; Troy Russell; Jared Conley; Michael Taylor; Giavoni Schifitto; et al. (Journal of NeuroVirology, 2011)

Cerebral metabolite abnormalities in human immunodeficiency virus are associated with cortical and subcortical volumes - Ronald A Cohen; Jaroslaw Harezlak; Assawin Gongvatana; Steven Buchthal; Giovanni Schifitto; Uraina Clark; Robert Paul; Michael Taylor; Paul Thompson; David Tate; Jeffery Alger; Mark Brown; et al. (Journal of NeuroVirology, 2010)

Cerebral metabolite abnormalities in human immunodeficiency virus are associated with cortical and subcortical volumes - Ronald A Cohen; Jaroslaw Harezlak; Assawin Gongvatana; Steven Buchthal; Giovanni Schifitto; Uraina Clark; Robert Paul; Michael Taylor; Paul Thompson; David Tate; Jeffery Alger; Mark Brown; et al. (Journal of NeuroVirology, 2010)

Genetic resistance to diet-induced obesity in chromosome substitution strains of mice - Lindsay C. Burrage; Annie E. Baskin-Hill; David S. Sinasac; Jonathan B. Singer; Colleen M. Croniger; Andrew Kirby; E. J. Kulbokas; Mark J. Daly; Eric S. Lander; Karl W. Broman; Joseph H. Nadeau (Mammalian Genome, 2010)

A comparison of tropical temperature trends with model predictions - David H. Douglass; John R. Christy; Benjamin D. Pearson; S. Fred Singer (International Journal of Climatology, 2008)
We examine tropospheric temperature trends of 67 runs from 22 ‘Climate of the 20th Century’ model simulations and try to reconcile them with the best available updated observations (in the tropics during the satellite era). Model results and observed temperature trends are in disagreement in most of the tropical troposphere, being separated by more than twice the uncertainty of the model mean. In layers near 5 km, the modelled trend is 100 to 300% higher than observed, and, above 8 km, modelled and observed trends have opposite signs. These conclusions contrast strongly with those of recent publications based on essentially the same data. Copyright © 2007 Royal Meteorological Society

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Map Scale Effects on Estimating the Number of Undiscovered Mineral Deposits - Donald A. Singer; W. David Menzie (Natural Resources Research, 2008)

Probability distributions for carbon emissions and atmospheric response - Clifford E. Singer; T. S. Gopi Rethinaraj; Samuel Addy; David Durham; Murat Isik; Madhu Khanna; Brandon Kuehl; Jianding Luo; Wilma Quimio; Kothavari Rajendran; Donna Ramirez; Ji Qiang; et al. (Climatic Change, 2008)

Characterization of Phosphorylation Dependent Antibodies To Study the Phosphorylation Status of the Tau Protein - David Singer; Daniela Volke; Ralf Hoffmann (International Journal of Peptide Research and Therapeutics, 2005)

The chemical cell biology of zinc: structure and intracellular fluorescence of a zinc-quinolinesulfonamide complex - M. Sarwar Nasir; Christoph J. Fahrni; David A. Suhy; Kevin J. Kolodsick; Christopher P. Singer; T. V. O'Halloran (JBIC Journal of Biological Inorganic Chemistry, 1999)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)